Hyperbaric exposure in rodents with non-invasive imaging assessment of decompression bubbles: A scoping review protocol. - Joshua Currens; Paul A Dayton; Peter Buzzacott; Virginie Papadopoulou (PLoS ONE)
Hyperbaric pressure experiments have provided researchers with valuable insights into the effects of pressure changes, using various species as subjects. Notably, extensive work has been done to observe rodents subjected to hyperbaric pressure, with differing imaging modalities used as an analytical tool. Decompression puts subjects at a greater risk for injury, which often justifies conducting such experiments using animal models. Therefore, it is important to provide a broad view of previously utilized methods for decompression research to describe imaging tools available for researchers to conduct rodent decompression experiments, to prevent duplicate experimentation, and to identify significant gaps in the literature for future researchers. Through a scoping review of published literature, we will provide an overview of decompression bubble information collected from rodent experiments using various non-invasive methods of ultrasound for decompression bubble assessment. This review will adhere to methods outlined by the Joanna Briggs Institute Manual for Evidence Synthesis and be reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses for Scoping Reviews (PRISMA-ScR). Literature will be obtained from the PubMed, Embase, and Scopus databases. Extracted sources will first be sorted to a list for inclusion based on title and abstract. Two independent researchers will then conduct full-text screening to further refine included papers to those relevant to the scope. The final review manuscript will cover methods, data, and findings for each included publication relevant to non-invasive in vivo bubble imaging.